Memoirs of Eighty Years - Hake, Thomas Gordon, 1809-1895 (Salt Lake City, UT : Project Gutenberg, 2018)
"Memoirs of Eighty Years" by Thomas Gordon Hake is a personal memoir written in the late 19th century. The book reflects on the author's long life, discussing his birth, family history, education, and various relationships that shaped his experiences. It offers a deep exploration of his childhood and early experiences, blending personal anecdotes with observations on society and culture. At the start of the memoir, Hake introduces himself and provides a glimpse into his early years, beginning with his birth in Leeds and the mention of his father's early death. He reflects on the complexities of family, noting the tradition and sometimes dubious origins of his lineage. He describes his encumbrances with education, the mischief he engaged in with his siblings, and the impactful influence of his mother. As Hake navigates through his childhood memories, he sets the stage for a life filled with evocative experiences, friendships, and the unfolding drama of growing up in a rapidly changing society. (This is an automatically generated summary.)
Release date is 2018-08-21
E-text prepared by the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Hake, Thomas Gordon, 1809-1895